Field emission of electrons from laser produced silicon tip arrays - Evtukh, A.A.; Kaganovich, E.B.; Litovchenko, V.G.; Litvin, Yu.M.; Fedin, D.V.; Manoilov, E.G.; Svechnikov, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The new preparation method of silicon tips with nanocomposite structure, namely laser modification of silicon is developed. The laser direct-write process has been applied, one by one (single) laser pulses formed the single rather uniform conical tips. In this process a silicon substrate is locally heated above its melting point by a pulse YAG:Nd³⁺ laser and translated by X-Y 100 mm resolution motor stages. Arrays with different tip distance, height and shape of tips can be produced by varying the condition of laser processing. The silicon tip arrays with distance between tips approximately 50 mm and height 0-100 mm with radius of the top about 1mm can be produced. As a result of intensive laser pulse influence, the silicon surface is very developed with many nanometer size protrudes on it covered with the nano-composite films (nc-Si-SiOx). Several samples were stain etched and porous silicon layers were formed on the surface. The electron field emission from laser produced silicon based nanocomposite structures into vacuum have been studied in dependence on conditions of their forming. The measurement of emission current were performed in the vacuum system which could be pumped to a stable pressure of 10⁻⁶ Torr. The diode measurement cell was used with constant emitter-anode spacing equal 20 mm. The field emission was obtained from nanocomposite structures in the drive voltage range from 100 to 1500 V and in the current range from 5nA to above 20 mA. The field emission current depends on the condition of silicon nanocomposite structure preparation strongly. The emission parameters: turn-on voltage, field enhancement coefficient and effective emitting area have been determined. The resonant tunneling phenomenon have been discovered on some samples with nanocomposite structures. As a rule, two or one resonant peaks have been observed. The current-voltage curves have assymetry in current maximum region which is determined with peculiarities of electron transport through resonant tunneling structures. These structures consist of Si quantum size nanocrystals in porous/or non-porous silicon oxide matrix. Due to the quantum-size effect, there are some energy levels in quantum well region, which cause increased tunneling probability under definite electric fields.